Acceptable or plagiarized? Thai university students’ evaluations of academic texts - Parinda Jantori; Daron Benjamin Loo (Penerbit Universiti Kebangsaan Malaysia, 2025)
University students are expected to develop an awareness of correct and ethical approaches to writing. This awareness includes the ability to determine the suitability of academic texts that are written based on references made to other sources. This study aims to examine Thai university students’ evaluation of the acceptability of academic texts that were paraphrased. Recent research from the region had indicated that university students had an incomplete understanding of acceptable academic writing. To further examine this phenomenon, this current study employs a mixed-methods approach where students had to rate the acceptability of three paraphrased versions of a text and provide their views on what constituted acceptable paraphrase through a survey. The survey was distributed to university students enrolled in an undergraduate-level academic writing course. A total of 104 students completed the survey by providing their ratings of acceptability. Among these, 89 students provided qualitative responses to share their views on what acceptable paraphrase is. The quantitative results indicated that many students were able to identify texts that were paraphrased completely; nonetheless, the qualitative responses revealed that students’ perceptions towards paraphrased revolved around form, that is, the substitution of words and reorganization of text. This reaffirmed existing studies from the Thai context, but it also provided new insights about how students viewed academic writing.